Interdisciplinary research paradigm of calligraphy and painting aesthetics and philosophy and its role in the construction of art theory system - Dong Wang (Trans/Form/Ação, 2025)
Calligraphy and painting aesthetics not only involves artistic creation and aesthetic experience, but also contains profound philosophical thinking, reflecting the unique oriental art view and world view. This paper adopts the method of philosophical analysis and interdisciplinary integration to re-examine the essence of calligraphy and painting aesthetics, and analyze its core value as a philosophical aesthetic practice, aiming to explore the interdisciplinary integration path of calligraphy and painting aesthetics and philosophy, and enrich and develop the theoretical system of calligraphy and painting aesthetics. This paper proposes that the essence of calligraphy and painting aesthetics is a philosophical aesthetic practice, the core of which is to construct an artistic ontology that transcends form with the dialectical unity of “skill” and “Tao”, thus opening up a unique oriental path for the cross-cultural dialogue and universal construction of the art theory system. The interdisciplinary research paradigm that combines calligraphy and painting aesthetics with philosophy can deepen the understanding of calligraphy and painting aesthetics and provide direction for the innovation of art theory under the background of globalization.